1988
DOI: 10.1007/bf01968080
|View full text |Cite
|
Sign up to set email alerts
|

Long-term depletion of histamine in guinea-pigs by administration of α-fluoromethylhistidine, a specific inhibitor of histidine decarboxylase; effect on the sensitivity of histamine receptors

Abstract: The effect of intraperitoneal administration of alpha-fluoromethylhistidine (alpha-FMH), a specific inhibitor of histidine decarboxylase, at a dose of 100 mg/kg twice a day for 6 weeks on the sensitivity of histamine receptors in the guinea-pigs was examined. The histamine contents in the ileum, heart and brain after the treatment decreased to about 54%, 83% and 9-62% (depending on the region), respectively, of those of controls. However, there were no significant difference in the histamine-induced contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…With one exception, neither we ( Fig. 1) nor others (Bouclier et al, 1983;Cacabelos et al, 1985Cacabelos et al, , 1987Fukuda et al, 1988;Itowi et al, 1989) depleted >80% of histamine in brain of any species after chronic cx-FMHis. One group (Fukuda et al, 1988) reported 90% depletion but only in cortex of guinea pig.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…With one exception, neither we ( Fig. 1) nor others (Bouclier et al, 1983;Cacabelos et al, 1985Cacabelos et al, , 1987Fukuda et al, 1988;Itowi et al, 1989) depleted >80% of histamine in brain of any species after chronic cx-FMHis. One group (Fukuda et al, 1988) reported 90% depletion but only in cortex of guinea pig.…”
Section: Discussionmentioning
confidence: 51%
“…1) nor others (Bouclier et al, 1983;Cacabelos et al, 1985Cacabelos et al, , 1987Fukuda et al, 1988;Itowi et al, 1989) depleted >80% of histamine in brain of any species after chronic cx-FMHis. One group (Fukuda et al, 1988) reported 90% depletion but only in cortex of guinea pig. This pool(s) of residual histamine is probably not attributable to mast cells, which, except for thalamus, are nearly absent in rat brain (Hough, 1988).…”
Section: Discussionmentioning
confidence: 89%